THE ROLE OF AUDIT QUALITY AS A MODERATOR IN THE DETERMINANTS OF EARNINGS MANAGEMENT - Ruci Arizanda Rahayu; Intan Kumalasari; Nihlatul Qudus Sukma Nirwana; Herman Ernandi (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This study aims to analyze the influence of audit committees, free cash flow, and tax planning on earnings management, with audit quality as a moderating variable, specifically in the consumer goods industry sector companies listed on the IDX during 2019-2023. Method: A quantitative approach is employed, utilizing multiple linear regression analysis and Moderated Regression Analysis (MRA), with data processed using SPSS 23 software. Results: The findings reveal that the audit committee does not significantly affect earnings management, free cash flow has a negative and significant impact, and tax planning shows a positive and significant effect. Audit quality does not moderate the relationship between the audit committee and free cash flow on earnings management, but it negatively moderates the relationship between tax planning and earnings management. Novelty: This study introduces tax planning as an independent variable and investigates the role of audit quality as a moderating factor in the context of earnings management, offering new insights into corporate financial practices.